An overview of beach morphodynamic classification along the beaches between Ovari and Kanyakumari, Southern Tamilnadu coast, India - Saravanan, S.; Chandrasekar, N.; Sheik Mujabar, P.; Hentry, C. (Морской гидрофизический журнал, 2011)
Beach morphology relates the mutual adjustment between topography and fluid dynamics. The morphological makeup of beach systems is not accidental because the arrangement and association of forms occur in an organized contextual space and time. Since the classification derived by Wright and Short (1983) obtained from the analysis of the evolution in a number of Southern Tamilnadu beach sites, beach systems are comprehended in terms of three-dimensional morphodynamic models that include quantitative parameters (wave breaking height, sediment fall velocity, wave period and beach slope) and boundary conditions for definable form-processes association (e.g. presence or absence of bars as well as its type). This has lead to the classification of beaches into three main categories relating the beach state observations with the physical forcing (Short, 1999) dissipative, intermediate (from the intermediate-dissipative domain to the intermediate-reflective domain) and reflective modes. Morphodynamic classification of beach types was based on the equations of Wright & Short (1984) (Dimensionless fall velocity – Dean Parameter).